Evaluation of Loneliness, Social Self-efficacy, and Burnout Relationship among Islamic University Students - Hendryadi Hendryadi; Nikita Puspita Ing Endit; Suryani Suryani; Hesti Kusumaningrum; Ani Cahyadi (Indonesian Journal of Islamic Education Studies (IJIES), 2022)
This study examines the impact of loneliness-related online learning on students during emergency remote teaching. Specifically, this study aims to: (1) evaluate the consistency between times of loneliness, burnout, and social self-efficacy, (2) examine the differences in the three measurements based on gender, and (3) examine the detrimental effects of loneliness on burnout and social self-efficacy of students at two Islamic state universities. Using a short-term longitudinal study design involving 237 students from two state Islamic universities. Data were analyzed using descriptive, comparative, correlation, and regression to test the proposed model. The results showed that loneliness and burnout at one point in time could consistently predict loneliness and burnout in the future. The comparative test results found differences in loneliness, burnout, and social self-efficacy based on gender, giving mixed results: significant differences were only found in loneliness (T2) and burnout (T2). Finally, there was no significant difference in social self-efficacy between male and female students at the two-time points.